1987
DOI: 10.1104/pp.85.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Supply and N2 Fixation in Soybean

Abstract: ABSTRACIWhen arrival of shoot supplied carbohydrate to the nodulated root system of soybean was interrupted by stem girdling, stem chilling, or leaf removal nodule carbohydrate pools were utilized, and a marked decline in the rates of CO2 and H2 evolution was (11,12,16,28) and are therefore unlikely to play a role in the support of nodule respiration. However, nodule starch and sugar levels decline under conditions of carbohydrate limitation (15,22,25)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
1
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(43 citation statements)
references
References 16 publications
2
38
1
2
Order By: Relevance
“…Second, regulation of maturation of nodule meristems into functional nodules might involve short distance and systemic interactions (CaetanoAnolles et al 1991 ;Francisco & Akao, 1993), as well as physiological controls imposed by the availability of carbon (Kosslak & Bohlool, 1984) and nitrogen (Atkins et al, 1989) for nodule development. The dependence of N^ fixation on the supply of carbohydrate from photosynthesis has been clearly demonstrated (Walsh, Vessey & Layzel, 1987). Singleton & van Kessel (1987) showed that, in the absence of mineral N, C flow to roots and nodules was affected by the export of fixed N from nodules.…”
mentioning
confidence: 99%
“…Second, regulation of maturation of nodule meristems into functional nodules might involve short distance and systemic interactions (CaetanoAnolles et al 1991 ;Francisco & Akao, 1993), as well as physiological controls imposed by the availability of carbon (Kosslak & Bohlool, 1984) and nitrogen (Atkins et al, 1989) for nodule development. The dependence of N^ fixation on the supply of carbohydrate from photosynthesis has been clearly demonstrated (Walsh, Vessey & Layzel, 1987). Singleton & van Kessel (1987) showed that, in the absence of mineral N, C flow to roots and nodules was affected by the export of fixed N from nodules.…”
mentioning
confidence: 99%
“…Walsh et al (1987) showed that the decline in nitrogenase activity caused by stemgirdling coincided with a decline in the total soluble-sugar content of nodules. Vessey et al (1988) found that the decline in nitrogenase activity caused by NO 3 Ϫ treatment coincided with a decrease in the size of the nodule starch pool and in the partitioning of the 14 C-labeled photosynthate to nodules.…”
Section: Effects Of Ar:o 2 Treatment On Suc and Starch Content Of Thementioning
confidence: 99%
“…There has been considerable interest in the possible involvement of nodule carbohydrates, particularly Suc, in the regulation of nitrogenase activity and nodule O 2 permeability (Walsh et al, 1987;Vessey et al, 1988;Weisbach et al, 1996;Gordon et al, 1997). Walsh et al (1987) showed that the decline in nitrogenase activity caused by stemgirdling coincided with a decline in the total soluble-sugar content of nodules.…”
Section: Effects Of Ar:o 2 Treatment On Suc and Starch Content Of Thementioning
confidence: 99%
See 2 more Smart Citations